Insect Pests in Agriculture Identifying and Overcoming Challenges through IPM - , Awanindra Kumar Tiwari (Archives of Current Research International, 2024)
Insect pests pose significant challenges to agricultural production worldwide, threatening food security and economic stability. Integrated Pest Management (IPM) offers a comprehensive approach to address these challenges sustainably. This abstract explores the principles and strategies of IPM, emphasizing its focus on minimizing environmental impacts and reducing reliance on chemical pesticides. Through biological control, cultural practices, mechanical control, and selective pesticide use, IPM aims to manage pest populations effectively while promoting biodiversity and long-term agricultural sustainability. By implementing IPM strategies, farmers can mitigate the impact of insect pests while fostering resilient and productive agricultural systems. Insect pests pose a significant threat to agricultural productivity worldwide. They can devastate crops, leading to substantial economic losses and threatening food security. Identifying and managing these pests effectively is crucial for sustainable agriculture. Integrated Pest Management (IPM) offers a comprehensive approach to address insect pest challenges while minimizing environmental impacts and reliance on chemical pesticides. Insect pests represent a persistent threat to agricultural productivity and food security globally. This abstract delves into the principles and practices of Integrated Pest Management (IPM) as a sustainable approach to address these challenges. IPM integrates various strategies, including biological control, cultural practices, mechanical control, and selective pesticide use, to manage pest populations effectively while minimizing environmental harm. By emphasizing monitoring, threshold levels, and selective interventions, IPM promotes the judicious use of pesticides and fosters ecosystem resilience. The abstract underscores the importance of IPM in promoting biodiversity, reducing chemical inputs, and ensuring the long-term sustainability of agricultural systems. Through the adoption of IPM principles, farmers can mitigate the impacts of insect pests while advancing environmentally conscious and economically viable agricultural practices.